The Illusion of the Presumption of Innocence in the Indonesian Criminal Justice System: A Hermeneutic Approach - Widiartana, Gregorius; Setyawan, Vincentius Patria (Civiliza Publishing, 2025)
Recent high-profile criminal cases in Indonesia have exposed significant gaps between the formal guarantee of the presumption of innocence and its practical application. This study aims to critically examine the “illusion” of the presumption of innocence in the criminal justice system, highlighting how public opinion and media coverage undermine this fundamental principle. The research adopts a hermeneutic approach, emphasizing interpretative analysis of legal texts, court decisions, and media representations to explore the dynamic interplay between normative law and social reality. Findings reveal that, despite its codification in the Indonesian Criminal Procedure Code, the presumption of innocence is frequently compromised in practice: suspects are often treated as guilty prior to judicial determination, influenced by sensationalist reporting and societal pressure. This discrepancy generates a gap between the formal text of the law and its lived reality, producing a sense of procedural injustice and eroding public trust in the judiciary. The study concludes that the presumption of innocence in Indonesia functions more as a normative ideal than an operational reality, particularly in cases that attract widespread media attention. Hermeneutic analysis demonstrates that restoring the principle’s substantive meaning requires a contextual understanding of law as both a normative and social phenomenon, alongside heightened awareness among legal practitioners, media actors, and the public regarding the ethical and procedural obligations inherent in criminal adjudication. The study underscores the necessity of integrating interpretive, human-centered approaches within legal practice to reconcile law’s formal prescriptions with societal realities and to strengthen the operational effectiveness of fundamental procedural rights.